Про один тип прикрас голови у слов'ян: за матеріалами Малоржавецького та Мартинівського скарбів - Володарець-Урбанович, Я.В. (Археологія і давня історія України, 2019)
У статті дається інтерпретація великих так званих «бобоподібних» пластин, із складу Малоржавецького та Мартинівського скарбів та визначається їх призначення як прикрас головного убору. The article analyses «bobo-similar» plates jewelry
from Malyi Rzhavets and Martynivka — four specimens.
In 1889 near the village Malyi Rzhavets was
found a small treasure of women’s jewelry. In 1907, in
the village Martynivka was found another treasure that
included the women’s and men’s jewelry and Byzantine
wares. Both complexes belong to the treasure of «Martynivka
» type or the first chronological hoard-group by
O. A. Shcheglova. One can assume the interpretation of these products as large temple ornament or decoration
of scythe. Quite similar (though not entirely similar) bronze ware — lamellar temporal rings — are known
in the antiquities of Roman times in Central Lithuania. The chronology of these jewelry — the phase B2 or
B2 / C1 — 100—230 А D. Finds from Central Lithuania and treasures from Malyi Rzhavets and Martynivka
differ in some design features, ornamental motifs and sizes. This can explain the chronological difference.